Pemanfaatan Biochar Tongkol Jagung Guna Perbaikan Sifat Kimia Tanah Lahan Kering - Zakarias Adrianto Mautuka; Astriana Maifa; Martasiana Karbeka (Peneliti.net, 2022)
One of the soil properties related to plant growth and development is soil chemical properties. Soil chemical components include soil pH, c-organic, cation exchange capacity, macro and micro nutrients. One of the efforts to improve soil quality that can be taken is the use of materials classified as soil enhancers, namely biochar. One of the plant biomass that can be used as a source of biochar is corn cobs. Corncob biochar is made by combustion of limited oxygen in a prepared combustion pit. The purpose of this study was to determine the effect of biochar from coconut shell on soil improvement in terms of soil chemical properties (pH, C-organic, N, P, K, C/N, CEC). The results of the study of soil chemical properties on the growth of shallot plants with the addition of biochar were able to increase soil nutrients such as pH, C-organic 6.81%, nitrogen 0.33%, phosphorus 0.10%, potassium 0.56%, and C ratio. /N 20.64 %, CEC 20.64 meq/100g.